ANALISIS MISKONSEPSI SISWA BERDASARKAN CERTAINTY OF RESPONSE INDEX (CRI) DALAM MENYELESAIKAN SOAL MATEMATIKA RANAH KOGNITIF MENGEVALUASI - Nurfiani, Merlin; Sunardi, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2018)
Abstract. This research aims to describe students’ misconception to solve evaluated problem based on Certainty of Response Index. It is a descriptive qualitative research. This research was conducted in SMPN 3 Jember with 67 students grade VIII. The instrument used test the higher order thinking of mathematics problems and guidelines for interview. The data collection methods were test and interview. The respondences were given test then the result of test would be categorized into lucky guess, lack of knowledge, understand concept, and misconceptions based on CRI. Based on data analysis, it can be conclude there are students’ misconceptions. In CRI scale 3, students had misconceptions in translation, systematic, strategy, and counting to solve evaluated problem. In CRI scale 4, students had misconceptions in translation, systematic, and strategy. In CRI scale 5, students had misconceptions in translation, systematic, strategy, and counting. Keywords: Misconception, Certainty of Response Index (CRI), evaluated mathematics problem